APOE4 genotype exacerbates the impact of menopause on cognition and synaptic plasticity in APOE‐TR mice. Issue 5 (23rd April 2021) - Pontifex, Matthew G.; Martinsen, Anneloes; Saleh, Rasha Noureldin M.; Harden, Glenn; Tejera, Noemi; Müller, Michael; Fox, Chris; Vauzour, David; Minihane, Anne‐Marie
Abstract: The impact of sex and menopausal status in Alzheimer's disease remains understudied despite increasing evidence of greater female risk, particularly in APOE4 carriers. Utilizing female APOE ‐TR mice maintained on a high‐fat diet background we induced ovarian failure through repeated VCD injections, to mimic human menopause. At 12 months of age, recognition memory and spatial memory were assessed using object recognition, Y‐maze spontaneous alternation, and Barnes maze. A VCD*genotype interaction reduced the recognition memory ( P  < .05), with APOE4 VCD‐treated animals unable to distinguish between novel and familiar objects. APOE4 mice displayed an additional 37% and 12% reduction in Barnes ( P  < .01) and Y‐maze ( P  < .01) performance, indicative of genotype‐specific spatial memory impairment. Molecular analysis indicated both VCD and genotype‐related deficits in synaptic plasticity with BDNF, Akt, mTOR, and ERK signaling compromised. Subsequent reductions in the transcription factors Creb1 and Atf4 were also evident. Furthermore, the VCD*genotype interaction specifically diminished Ephb2 expression, while Fos, and Cnr1 expression reduced as a consequence of APOE4 genotype. Brain DHA levels were 13% lower in VCD‐treated animals independent of genotype. Consistent with this, we detected alterations in the expression of the DHA transporters Acsl6 and Fatp4 . Our results indicate that the combination of ovarian failure and APOE4 leads to an exacerbation of cognitive and neurological deficits.